Short Course of Antibiotic Therapy for Gram-Negative Bacilli Bacteremia in Patients with Cancer and Hematopoietic Stem Cell Transplantation: Less Is Possible - Fabián Herrera; Diego Torres; Alberto Carena; Federico Nicola; Andrés Rearte; Elena Temporiti; Laura Jorge; Ricardo Valentini; Florencia Bues; Silvia Relloso; Pablo Bonvehí (Microorganisms, 2023)
Data about short courses of antibiotic therapy for Gram-negative bacilli (GNB) bacteremia in immunosuppressed patients are limited. This is a prospective observational study performed on adult patients with cancer and hematopoietic stem cell transplant (HSCT) who developed GNB bacteremia and received appropriate empirical antibiotic therapy (EAT), had a clinical response within 7 days and survived 48 h after the end of therapy. They received antibiotic therapy in the range of 7–15 days and were divided into short course, with a median of 7 days (SC), or long course, with a median of 14 days (LC). Seventy-four patients were included (SC: 36 and LC: 38). No differences were observed in baseline characteristics or in the presence of neutropenia: 58.3% vs. 60.5% (p = 0.84). Clinical presentation and microbiological characteristics were similar in SC and LC, respectively: clinical source of bacteremia 72.2% vs. 76.3% (p = 0.68); shock 2.8% vs. 10.5% (p = 0.35) and multidrug-resistant GNB 27.8% vs. 21.1% (p = 0.50). Overall, mortality was 2.8% vs. 7.9% (p = 0.61), and bacteremia relapse was 2.8% vs. 0 (p = 0.30). The length of hospitalization since bacteremia was 7 days (interquartile range (IQR), 6–15) for SC and 12 days (IQR, 7–19) (p = 0.021) for LC. In the case of patients with cancer or HSCT and GNB bacteremia who receive appropriate EAT with clinical response, 7 days of antibiotic therapy might be adequate.